2015
DOI: 10.1371/journal.pone.0132774
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Remission in Gulf War Illness: A Simulation-Based Approach to Treatment Design

Abstract: Gulf War Illness (GWI) is a chronic multi-symptom disorder affecting up to one-third of the 700,000 returning veterans of the 1991 Persian Gulf War and for which there is no known cure. GWI symptoms span several of the body’s principal regulatory systems and include debilitating fatigue, severe musculoskeletal pain, cognitive and neurological problems. Using computational models, our group reported previously that GWI might be perpetuated at least in part by natural homeostatic regulation of the neuroendocrine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 46 publications
6
31
0
Order By: Relevance
“…We found white blood cell counts and blood biomarkers related to inflammation could discriminate groups that did or did not meet the current symptom-based criteria for case definition of GWI. Our observations are consistent with conclusions expressed in recent literature reviews that immune dysregulation/neuroinflammation are components of the pathobiology of GWI [ 28 , 29 ]. Appropriate assays for the presence of chronic inflammation could provide objective evidence that would facilitate the diagnosis of GWI+.…”
Section: Discussionsupporting
confidence: 93%
“…We found white blood cell counts and blood biomarkers related to inflammation could discriminate groups that did or did not meet the current symptom-based criteria for case definition of GWI. Our observations are consistent with conclusions expressed in recent literature reviews that immune dysregulation/neuroinflammation are components of the pathobiology of GWI [ 28 , 29 ]. Appropriate assays for the presence of chronic inflammation could provide objective evidence that would facilitate the diagnosis of GWI+.…”
Section: Discussionsupporting
confidence: 93%
“…While in our previous studies the profile of ME/CFS in women suggested targeting the Th2 immune cytokines followed by inhibition of the glucocorticoid receptor system, 69 this predicted drug course has not yet been optimized. 71…”
Section: Discussionmentioning
confidence: 99%
“…A simulation algorithm, as described previously in Craddock et al ( 2015 ), was used to analyze the response of the neuroimmune model to external perturbations. Briefly, from any initial state, allowable state evolutions are determined based on the 3-valued logic described in Equation (2).…”
Section: Methodsmentioning
confidence: 99%
“…To identify a robust intervention capable of moving the neuroimmune signaling system from an alternate, potentially pathological, mode of regulation to that of typical health, putative treatment strategies were simulated. For each candidate treatment strategy, simulations were conducted to evaluate the likelihood of returning the system from an alternate stable regulatory state, to the stable state of typical health, as described previously in Craddock et al ( 2015 ). Specifically, starting from the alternate regulatory stable state, a variable affected by the putative treatment was shifted according to the treatments mode of action: −1 (suppressing), 0 (untreated), and 1 (elevating).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation